Correlation between Tooth Position Parameters and Apical Fenestration: A Cone-Beam Computed Tomography Study - Ferrari, Carlos Henrique [UNESP]; de Carvalho, Lara Steffany [UNESP]; Rocha, Caroline Trefiglio [UNESP]; Abu Hasna, Amjad [UNESP] (MDPI, 2024)
This study aimed to assess the relationship between apical fenestration—a defect in the alveolar bone involving the root apex—and tooth position in all tooth groups, excluding the third molars, utilizing cone-beam computed tomography (CBCT) images. A total of 800 CBCT scans (400 maxillary and 400 mandibular) from patients undergoing various treatments were examined by a single professional (radiologist and endodontist). Statistical analyses, including the chi-square test or Fisher’s exact test, were conducted using R software 2.7.3 (R Foundation, Vienna, Austria). Results indicated a significant association (p ≤ 0.05) between apical fenestration and tooth position. In the upper teeth, apical fenestrations were notably present in the mesio-buccal (17.17%) and disto-buccal (11.07%) roots of the first molars. Conversely, apical fenestrations in the lower teeth were relatively less frequent. The study revealed a negative correlation between apical fenestration and mesial inclination, rotation, and extrusion in the upper teeth. However, a positive correlation was observed between apical fenestration and lingual inclination in the upper teeth. In conclusion, this study illuminates the distribution of apical fenestration and its correlation with tooth positions, offering insights into factors influencing this defect in dental anatomy. The findings enhance our understanding of nuanced relationships between tooth position and apical fenestration in the upper and lower dental arches.
Keywords: apical fenestration; cone-beam computed tomography; tooth position